Comparison of Conventional and Microwave Heating - Cristóbal Valverde; Margarita M. Rodriguez-Garcia; Esther Rojas; Rocio Bayon (SolarPACES Conference Proceedings)
Carnot batteries (or Power-to-Heat-to-Power systems) are capable of increasing the use of electricity from photovoltaic or wind power plants to achieve decarbonisation of the electricity sector. To decouple electricity production from demand, these renewable power plants can be connected to the thermal energy storage system of a concentrated solar thermal power plant via electric heaters. As an alternative to electric heaters, microwaves are studied as a volumetric and selective heating method, avoiding the limitations of the Joule effect conventional heating when having solar salt (non-eutectic mixture of 60 wt % NaNO3 and 40 wt % KNO3), which is a storage medium with low thermal conductivity, working at a temperature very close to its affordable maximum temperature without degradation. In this work, the two heating methods are compared both experimentally and numerically. At experimental level, a microwave oven and a muffle furnace are used to record energy consumption and time for a common objective. Additionally, different crucible materials were used to test their suitability with microwaves. Only quartz glass was validated for microwave heating, while the porcelain and alumina based materials (Corundum and Alsint 99.7) failed while exposed to microwaves. Compared to conventional heating, heating solar salt with microwaves saved fifty minutes of time and ninety percent of consumption. These experiments were validated by numerical simulations, showing a different distribution in each experiment.